First contribution to the knowledge of coralline algae distribution in the Slovenian circalittoral zone (northern Adriatic) - Falace, Annalisa (Annales. Series historia naturalis, 2011)
Authors present new data on the coralline algal flora from Slovenia. They come from recent inspection of the Slovenian part of the Gulf of Trieste where peculiar communities, such as the biocoenosis of the coastal detritic bottom, the agglomeration of bioconcretions known in the area under the name of "trezze" or "tengue", and the bank of Mediterranean stony coral Cladocora caespitosa, occur. In such communities 11 coralligenous red algae were found. Five of them, Hydrolithon boreale, Lithothamnion minervae, L. philippii, L. sonderi and Neogoniolithon brassica-florida are newly recorded for Slovenia.
Keywords: circalittoral; cirkalitoral; Cladocora caespitosa; coralline algae; koraligene alge; northern Adriatic; severni Jadran; Slovenia; Slovenija